Walking in-between memories :|everyday and affective encounters in the memory walks and facing the past - Barın, Damla. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2022., 2022)
This thesis is about the everyday experiences of facing the past through memorialization practices. It takes the Memory Walks as a case study where the participants encounter histories and memories through collective walking and storytelling in the city. Based on theories of everyday life, place, performance/performativity, memory, and affect, and ethnographic fieldwork as a research method, the thesis reveals how the Memory Walks open the door to invisible histories and memories, new ways of experiencing the city and ways of feeling and knowing about difficult pasts. Bringing together urban experiences, walking practices, and performances of memory, the thesis aims to expand the legal, policy-related, and nation-state-centered understandings of facing the past and offers a framework of the everyday. Arguing that facing the past is an open-ended process, the thesis looks at the everyday and affective experiences in the Memory Walks on two main axes. First, it demonstrates the role of walking in shaping people’s relationships with the city and making urban places by examining the performative and critical aspects of walking. Second, it explores the role of emotions in memorialization practices and analyzes the affective encounters in the Memory Walks by examining ways of feeling and knowing connected to facing the past. Exploring the two axes, the thesis asks: How are the everyday and affective encounters that emerge through memorialization practices connected to the experiences of facing the past in the everyday?
Keywords: Collective memory.; Memorialization.